Solve for x (complex solution)
x=\frac{-5487+\sqrt{236985407}i}{51682}\approx -0.106168492+0.297866382i
x=\frac{-\sqrt{236985407}i-5487}{51682}\approx -0.106168492-0.297866382i
Graph
Share
Copied to clipboard
25841x^{2}+5487x+2584=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-5487±\sqrt{5487^{2}-4\times 25841\times 2584}}{2\times 25841}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 25841 for a, 5487 for b, and 2584 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-5487±\sqrt{30107169-4\times 25841\times 2584}}{2\times 25841}
Square 5487.
x=\frac{-5487±\sqrt{30107169-103364\times 2584}}{2\times 25841}
Multiply -4 times 25841.
x=\frac{-5487±\sqrt{30107169-267092576}}{2\times 25841}
Multiply -103364 times 2584.
x=\frac{-5487±\sqrt{-236985407}}{2\times 25841}
Add 30107169 to -267092576.
x=\frac{-5487±\sqrt{236985407}i}{2\times 25841}
Take the square root of -236985407.
x=\frac{-5487±\sqrt{236985407}i}{51682}
Multiply 2 times 25841.
x=\frac{-5487+\sqrt{236985407}i}{51682}
Now solve the equation x=\frac{-5487±\sqrt{236985407}i}{51682} when ± is plus. Add -5487 to i\sqrt{236985407}.
x=\frac{-\sqrt{236985407}i-5487}{51682}
Now solve the equation x=\frac{-5487±\sqrt{236985407}i}{51682} when ± is minus. Subtract i\sqrt{236985407} from -5487.
x=\frac{-5487+\sqrt{236985407}i}{51682} x=\frac{-\sqrt{236985407}i-5487}{51682}
The equation is now solved.
25841x^{2}+5487x+2584=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
25841x^{2}+5487x+2584-2584=-2584
Subtract 2584 from both sides of the equation.
25841x^{2}+5487x=-2584
Subtracting 2584 from itself leaves 0.
\frac{25841x^{2}+5487x}{25841}=-\frac{2584}{25841}
Divide both sides by 25841.
x^{2}+\frac{5487}{25841}x=-\frac{2584}{25841}
Dividing by 25841 undoes the multiplication by 25841.
x^{2}+\frac{5487}{25841}x+\left(\frac{5487}{51682}\right)^{2}=-\frac{2584}{25841}+\left(\frac{5487}{51682}\right)^{2}
Divide \frac{5487}{25841}, the coefficient of the x term, by 2 to get \frac{5487}{51682}. Then add the square of \frac{5487}{51682} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{5487}{25841}x+\frac{30107169}{2671029124}=-\frac{2584}{25841}+\frac{30107169}{2671029124}
Square \frac{5487}{51682} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{5487}{25841}x+\frac{30107169}{2671029124}=-\frac{236985407}{2671029124}
Add -\frac{2584}{25841} to \frac{30107169}{2671029124} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{5487}{51682}\right)^{2}=-\frac{236985407}{2671029124}
Factor x^{2}+\frac{5487}{25841}x+\frac{30107169}{2671029124}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{5487}{51682}\right)^{2}}=\sqrt{-\frac{236985407}{2671029124}}
Take the square root of both sides of the equation.
x+\frac{5487}{51682}=\frac{\sqrt{236985407}i}{51682} x+\frac{5487}{51682}=-\frac{\sqrt{236985407}i}{51682}
Simplify.
x=\frac{-5487+\sqrt{236985407}i}{51682} x=\frac{-\sqrt{236985407}i-5487}{51682}
Subtract \frac{5487}{51682} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}